Doctor-Patient Relationship as Dancing a Dance - Luis Turabian Jose (Journal of Family Medicine, 2018)
The transcendence of the doctor-patient relationship is given by the confirmed fact of its influence on the results of health care. Several models of doctor-patient relationship can be described, but evidence of improved compliance, satisfaction and recall of physician information has been found in patient-centered consultations. Since these concepts of doctor-patient relationship and patient-centered consultation have multiple facets, they are complex to understand and teach. Using a metaphor is a tool that can be useful in these situations. We could say that the
Keywords: Physician-Patient Communication